Simulation of condensation unit in ASPEN PLUS - A. A. Mikhin; V. V. Sergeev (Известия высших учебных заведений: Проблемы энергетики)
The article discusses the scheme of deep utilization of the heat of flue gases. It has been established that in boiler units operating on natural gas, the only way to significantly improve the use of fuel is to deeply cool the combustion products to a temperature at which it is possible to condense the maximum possible portion of the fumes contained in the gases. To analyze the main energy indicators of the condensing unit and optimize its operating modes, a priority scheme was simulated in Aspen Plus. In this scheme, there are tees, heat exchangers and a reactor (boiler furnace). The configuration of tees (mixers) is carried out by setting the costs or fractions of two flows entering or leaving the element. The boiler furnace is modeled as a Gibbs reactor, which calculates the chemical and thermodynamic equilibrium by minimizing the difference in the Gibbs energy of the products and the starting materials. Using the Aspen Plus computer program, the condensation unit circuit was simulated at the PTVM-100 boiler unit with the specification of the optimal operating parameters of material flows and heat exchange equipment. The calculations show that when using a condensing boiler, a triple energy effect is achieved: the physical heat of the flue gases is used; the latent heat of vaporization released during condensation is used; the condensate released from the flue gases is used.